Unilateral balance performance in female collegiate soccer athletes - Thorpe, J. L.; Ebersole, K. T. (The Journal of Strength and Conditioning Research, 2008)
The Star Excursion Balance Test (SEBT) is a unilateral balance task designed to evaluate dynamic postural control. This investigation explored the relationship between limb preference, strength, and performance on the SEBT in NCAA Division I, female collegiate soccer athletes (nonsoccer, n = 11; soccer, n = 12). Each participant completed maximal, concentric test efforts at a velocity of 90°/s for supine ankle dorsiflexion (ADF) and plantarflexion (APF) and at 60°/s for the seated leg extension (LE) and flexion (LF) and supine hip extension (HE) and flexion (HF). In addition, participants performed maximal SEBT reaches in the anterior, medial, and posterior directions. All testing was completed on both limbs. These results indicate that SEBT performance is similar for both limbs in both groups. The soccer group, however, reached significantly farther than the nonsoccer group, suggesting that the SEBT may be sensitive to training status and/or sport-related adaptations. The concentric strength results indicate that despite group differences in all strength tests, strength in general was not highly correlated to SEBT performance. Thus, neuromuscular factors above and beyond strength may have accounted for the group differences in SEBT performance. The SEBT may be a useful tool for determining the relative effectiveness of an intervention designed to improve postural control.